(untitled) - YULIANTI, ERNA (Language Horizon: Journal of Language Studies, 2014)
POLITENESS STRATEGIES IN REQUEST AND COMMAND USED BY AUNG SAN SUU KYI TO RULE BURMESE IN MOVIE “THE LADY” Erna Yulianti English Literature, Faculty of Language and Art, State University of Surabaya, nana_jouly@yahoo.com Advisor: Dian Rivia Himmawati, SS., M.Hum dianrivia@gmail.com Abstrak The major aims of this study are to analyze the positive and negative politeness strategies, to analyze the characteristics of two types of politeness strategies concerned to request and command utterances, and to know how strategies that subject used influence the responses of addressee. The subject of this study is Aung San Suu Kyi, the main character of film “The Lady”. The data were taken from subject’s utterances classified by Brown and Levinson’s theory of positive and negative politeness strategy, theory of request and command by Blum-Kulka, and theory of power language by Fairclough. The method of this study is qualitative approach. Pragmatics and critical discourse analysis are used to interpret the data analyzing. This study relates to the power language. The power means how the strategies influence the responses in the communication. As results, it’s found that there are three main results. First, San Suu Kyi used both positive and negative politeness with various sub-types strategies in the utterances. Second, there are politeness characteristics built by San Suu Kyi through request and command utterances. The characteristics were presented by sub-categories of request sequences and three level of command. And the last, the strategies that subject used have great impact to the responses were given by addressee. Within analyzed the responses, this study used three constrains of power language (subject, relation, content). They were found that subject of the study has influential and instrumental power which influence addressees to give positive responses. This study also creates some findings as final result of data analyzing. The findings concerned on differential forms of three main results analyzed. Key words: politeness strategy, positive politeness, negative politeness, request, command, power language INTRODUCTION Today women contributed to the political sector. Now, the achievement of the women to share ideas and thoughts had strong influences to the society. Women had opportunity to be leader or head as same as man. Many of them were successful to bring the big change, as example were the iron lady, Margaret Tacher – prime minister of Great Britain, Aquino – president of Philipines, and Aung Saa Suu kyi (Suu) - politician who successful brought Burmese changed political guidance from military government to the democracy. It means that women had political power to influence the subordinates or society. Women successfulness was not separate from the strategy used. How to maintain and control society, how to ensure society about the ideas, and how to make society believed in what contributed were some strategies used by politician, especially woman politician. Here, the role of language was significant to gain the strategies. Therefore woman tend to use different type of language than that man. Based on Holmes (2001) one of the types of strategies was politeness, because women were more polite than man in building communication with hearer. From that issue, politeness became good character of using language point of view. Because of the function of politeness applied which not only a duty but also a favor, it would be interesting to lift politeness as topic analyzed. Politeness was one of strategies usually used to cover some goals, it also became attribution in communication. Compare to the other language strategies, politeness had higher position in its function to achieve good responses than another. It is believed that politeness is a principle of language identified character. Someone would define as good character, moreover woman, if she used polite language. By contrast, someone who lack of polite words in speech, it means (s)he has bad character. Both people and its character can be measured by the language used, because in the societies many people argued that hearer more paid attention to the speaker who had good personal character with polite way to speech. The language use has many utterances to gain wants, like apologize, warning, persuasion, invitation, thank, command, and request. They were probably used in language applied. A research conducted by Wagner used apologized related to politeness too. It could identify known or stranger participant in social relationship. It would be different from request utterances which could identify how strong speaker wanted to something. And command could identify how important speaker’s position to obligate something. Because of these order more appropriate to the notion of power language which they would tend to state the ideas or thoughts in request and command statements. Asking for agreement of some programs or plans was tendency of “request” order used. Leading for conducting movement like warning or instruction of public campaign was tendency of “command” order used. The use command and request in politeness applied would influence to the hearer responses, it means good responses referred to the good speaker. Because of that, Aung San Suu Kyi put as strong politician figure which had good speaker. There were other figures that may have same position as Suu, such as Margaret Techer who successes in dominating house of representative for several periods or Aquino who became the first woman president in Philippine, but, the achievements of Suu more influential than another. Suu was politician of pro democracy in Myanmar where societies appreciate to the figure who brings democracy into the country. As politician who had great opportunities to unite Burmese under democracy consciousness, the request and command stated were intentioned by Burmese. The struggles also considered as defensive movements to the government created democracy in that country. The efforts to unite Burmese conducted in the prison and separated from family. This position made Suu appreciated by people as figure of politician who led Burmese to the democracy who has great opportunities to unite Burmese under democracy consciousness, even the speeches and talks were very influential. Every utterances used, stated Suu in high position, So that, it would be interesting to take Suu as subject of the research. Based on issues that the women more polite than men, the politeness used in request and command could identify the power, and the importance position of Suu as politician led this study to find (1) what are types of politeness strategies used by Aung San Suu Kyi, (2) what are types of request and command used by Aung San Suu Kyi, and (3) how does Aung San Suu Kyi influence addressees in order to get good responses. Those reasons decided that politeness strategies used by Aung San Suu Kyi in request and command to rule Burmese as title of this study. This study related to the other studies. Since it analyzed utterances, pragmatic and critical discourse analysis (CDA) were theory used. According to Schiffrin (1994:41), discourse can be approached to the pragmatic study. To prove her argument she describe three definitions of discourse, they are “the language above the sentence”, “language use” and “utterances”. Discourse can research how speakers produce utterances, what strategy that speakers used, what the goals are, and how speakers influence hearer to get good responses. Fairclough (2012:452) states that CDA investigates the social phenomena which are complex. In terms of the concept of social practice, CDA criticizes social practices such as; social subjects, social relations, instruments, objects, strategies in using language, values, etc. He emphasizes that studying discourse in society means giving focus on power, dominance and the way these reproduced by social member through talks. Those three modes often appear in social communication practices. These linguists had similar arguments which utterances spoken in society can be analyzed the meaning through discourse and pragmatics. The other study was politeness strategy in positive and negative which both of them had their own sub-strategies. Based on Brown & Levinson (1987) positive politeness was positive self-image of addressee. Doing FTA by using this strategy means that speaker (S) considers that (s)he wants hearer (H)’s wants. E.g by threatening H as a member of his/her group, a friend, or a person whose desire and personality traits are known and liked. In positive politeness, the area of redress is extended to the appreciation of H’s desires or the expression of similarity between S’s and H’s desires. Negative politeness had at least ten sub-strategies. Here, this study provides seven sub strategies, they are: be conventional indirect, go on record (incurring debt/no indebting) H, apologize, don’t coerce H, impersonalize S and H, give deference, and be pessimistic. Yule (1997) assumed that negative politeness is oriented to satisfy H’s negative face, basic want of H is to be free and unimpeded. It meant that the speaker recognized and respected the addressees’s freedom of action and would not (or would minimally) impede it. be optimistic, include both S and H in activity, give gifts to H, avoid disagreement, offer promise, give reason, use in-group identity maker, asserts/presuppose S’s knowledge of concern for H’s wants, seek agreement and exaggerate. Since the strategies used by subject [Suu] focused on request and command that theory is needed to identify the types. Based on the Blum-kulka (1987), request was part of speech act performed when a speaker wants a person (the hearer) to do something. Some types of categories provided in request utterances were: query preparatory, strong hints, mild hints, obligation statement, hedge performative, and suggestory formulae. In command utterance, Robinson (1972) argued that it referred to activities involved in the regulation when speaker produced command to fulfill by hearer. Blum-kulka gave guidance of three level of commands to identify how powerful them used for to be fulfilled by hearers. Most direct: command which directly pointed out the topic, usually imperative Conventional indirect: command which contained command form, but it is added by supporting sentence in order to decrease the directness Inconventional indirect: command which did not command form, but the essential meaning was command. To analyze the hearers’ responses this study related politeness strategies to the power. Fairclough (1989) argued that power relationship has big scope which power can appears from subject, society, status, relationship etc. he gave power indentifying through three constrains that useful to identify whether speakers have power language or not. There are three types of such constrains on: Contents on what is said or done Relations. Social relations people enter into in discourse Subject or the subject positions people can occupy. RESEARCH METHOD This study was conducted by using qualitative approach, as Litosseliti (2010) said that the study of text or talk (spoken discourse) used to analyze how the politeness strategy through utterances which was spoken by main character employing the approach of politeness theory that concern with positive and negative politeness and their influence related to the power language. This included developing a description of an individual or setting, analyzed data for themes or categories, and finally making an interpretation or drawing conclusions about its meaning personally and theoretic. The data source of this study was taken from a film titled The Lady which released on 2011. The film based on true story of pro-democracy politician in Myanmar. Command and request utterances were chosen as data taken from the main - character Auu Saan Suu Kyi and added by conversational sequences. The instrument of the data was covering material by analytical thoughts, therefore media was very important in conducting this study, for instance; visual media recorder. Based on Erickson (in Litosseliti: 2010) the data were collected by using systematic attention to meaning. First step was collecting and logging data, it means logging processes were viewing film and note analytical thoughts. Second part was viewing data as research team, it means organizing them into generated criteria. Third part was sampling data, it more focus on what stands out. And the last was transcribing data by using a range of descriptive dimensions. Data selecting were utterances selection of Suu which concerned to the request and command utterances. The data selected in to sub-types of (positive and negative politeness) also selected in to sub-categories of request and command. For example: no. acts data politeness characteristics (+) (-) request command 1. 15 “Give it to me!” Give gifts to H Most direct DATA ANALYSIS 1. The Types of Positive and Negative Politeness Used by Aung Saan Suu Kyi This part analyzed about types of positive and negative politeness strategies used by Aung Saan Suu Kyi. There were many types which have their own characteristics. It tend to analyze which utterances that belong to sub types of positive politeness and which utterances that belong to sub of types negative politeness. 1.1 Positive politeness Conventional indirect that used by Suu in her utterances are an unambiguous sentences or phrases which contextually have different meaning from literal meaning. In many contexts there are many sentences which are conventionally understood differently from its literal meaning, like stated on the data below. Data 35: (A)Ne-win’s delegation: “How was Mr. Aris? I’m sorry to hear that” (B)Suu: “((ne-win’s delegation comes to drive suu away)) it is not your question, Norway government borrowing us an air ways ambulance, Dalai Lama send one of the best doctor to follow Michel Suu said; “it is not your question,” this utterance encodes the clash of desire, Suu’s desire of going on record states as the desire of going off record. In this condition means suu knows everything that would be said by delegation. As information, before suu utter that, the delegation ask about the condition of Suu’s husband who suffered from cancer, but suu does not answer the question by saying good or not too good for example, There are extended desire that suu want to achieve, but she gives long explanation “Norway government borrowing us an air ways ambulance, Dalai Lama send one of the best doctor to follow Michel”. Here, this information used to make hint critics to the government about why see can not meet her husband while the facilities provided. In these cases the utterances have different meaning from literal meaning. b. Go on record as (incurring debt/no indebting) H, This strategy suggests speaker [S] may redress his FTA by explicit conveying his indebtedness to hearer [H] or disclaiming any indebtedness of H. this extracts below are type of go on record without indebting H. Data 2: (A)Suu: “Be a good boy, help your father when I’m not here” (B)Children: “Yeah…” The extract contained directive form since the speaker used them in direct way. Directives are concerned with getting people to do things. The speaker which expresses directive force varies in strength. Direct typically signed by using of verb at the beginning of the sentences like be, help, don’t, tell, go, stay here. Identifying directive should pay attention to the intonation and tone of voice used by the speaker. There were no claiming indebting hearer, because hearer seems know that what S wants are like a duty that they should do. c. Apologize, This strategy to show that S did not mean to impinge H apologizing. By apologizing for doing FTA, S indicates her reluctance to impose on H’s negative face. Brown and Levinson suggested to communicate regret or reluctance to do an FTA. The first way is S frankly admits that she is impinging H’s negative face. This strategy applies in this extracts below. Data 4: (A)Leo: “Don’t you mind to call me every time you need (B)Suu: “ Yes I will, thank you for everything uncle Leo The word thanks here does not mean thanks as usual, S implicitly says “sorry” under function of notion thanks. This utterance more sounds sorry than thanks, because the condition and situation tend support speaker to say “I’m sorry to bother you with everything” than “thank you for everything”. H has been done everything to help S fulfill her desire in impossible and critics situation, but H can do it well, so that S showing respect to H’s conducts because of the bothering. Then, S has to be sorry for it. In spite of saying thanks, it is contains of sorry implicitly. S does it strategy to not impinge H. d. Don’t coerce H [hearer], another way to satisfy H’s negative face is by avoiding coercing hearer especially when the FTA involves predicating act of H such as requesting help or offering something which needs H’s acceptable. This condition can be created by explicity giving H the opinion not to do the expected act Data 5: (A)Suu: “What are you doing?” ((stop the activist)) (B)The activist: “we have to go” The data above contain strategy. Speaker avoids coercing H because of the utterances involves of predicate “do”. In this condition, S asks for request to H “don’t” do something. e. Impersonalize S and H, Pluralizing ‘I’ and ‘you’ is another technique to save H’s negative face. According to the Brown and Levinson (1987:189) it seems to be very general in many languages that the use ‘you’ (pl) pronoun to refer to a single person is understood to show deference (P) or distance (D). Hence ‘we’ and ‘you’ can serve for ‘I’ and ‘you’ (sing) respectively to give respect to single referent ‘we’ is possibly the conventionalized polite form more appropriate to formal situations [campaign] and negative politeness. because it usually use in formal speech like campaign. S bring the name of party under the name of togetherness Data 12: Speech 1[Suu] Buddhist, Burmese, today, we meet here in order to unite 1our desire for freedom, we want the world look us for it. The world should hear our voice to be democratic state with multiparty. For those aim, we [NLD] want you to know….. f. Give deference, This strategy suggest that S [Suu] considers H [husband] being in higher social status than her. There are two ways in the realization of this strategy; one in which S humbles and lowers himself and the other in which S raises H’s position or treats H as superior like in the extracts below. people use thanks for showing the great affection to bother about something. Data 26: (A)Suu: “Thanks for everything, I can’t do anything without you, I will be right here Mikey, don’t worry, prior the boys.” (B)Husband: “sure I will, you have long trip, be sure to eat well, keep your health” The negative politeness shows in (data 26), those utterances appear when she talks to her husband. Before the utterances are spoken, there are a lot of things have done by her husband for helping her, so the words thanks for everything convey a lot of meaning. First, beside it applies thank for all of things, it also apply an apology. Suu feels that everything that she burdens to her husband is a load. In that case she tries to apologize by using thanks, not in sorry, because thanks listened respect, being honor to the husband. g. Be pessimistic, This strategy suggests that S may explicitly express a doubt that H is not likely to do his expected act. It means that S should be pessimistic about H’s response. Data 34: (A)Suu: “ As you, should I be there?” (B)Husband: “no, no Suu, you shouldn’t, don’t think about it” Strategy used by Suu in the data above contains modality form. In As you, should I be there? S making question with pessimist desire, she arranges it to hide the pessimistic with saving way by using modality. Modality is irrealis, counterfactual forms would, could, might etc are more polite than ability or future-oriented variant can and will. 1.2 Negative politeness a. Be optimistic, Strategy that assumes H wants what S wants for himself (or for both of them) and H will help S to obtain it. On contrary of strategy offers promise, This strategy suggests S being presumptuous or optimistic allows S to put pressure on H to cooperate with him. verb placed in the beginning of utterances “stay” possible indicates optimistic reason, it is caused by communication situation and hearer. Data 21: (A)Party member: ((take the gun on)) (B)Suu: “No, don’t think about it, there’s no bullet, we still continue. Stay calm, stay calm, stay here.” ((walk forward face soldiers with guns pointed her)) The situation at that time is S and her party member held a meeting for campaign, but, the meeting is sabotaged by military government. They bring ready gun and weapon to stop the meeting. S as leader of the meeting, is optimist that they are not too danger to fight. So that S confidently says to the H [one of her party member] like in “No, don’t think about it, there’s no bullet, we still continue. Stay calm, stay here.” b. Include both S and H in activity, Including both S and H in the activity is another way to perform cooperative strategy. An inclusive ‘we’ form which S really means ‘you and me’ is commonly used to make H involve in S action thereby redress FTA, some common examples are We can start it (data 10). This strategy is often use to soften requests where S pretend the requested thing too, and offers where S pretends as if S were as eager as H to have the action. At data 10, S may utters it Data 10: (A)Guests: “we come to ask you to discuss many things that occur recently Daw Suu” (B)Suu: “We can start it? for inviting the guests who come to talking about democratic crisis. Since S interested in the meeting and the topic talked, S gratefully accepts the guests, then S expresses inviting H [guests] by using direct request which in fact means “well, why don’t we start it now?”. The inclusive “we” used to show that between S and H are cooperate in same purpose. c. Give gifts to H, This strategy is to satisfy H’s face S may grant H what H wants e.g; by giving gift H. Not only tangible gift, which indicates that S knows H’s wants them to be fulfiled, but also human relations wants like the wants to be liked, admired, cared about, understood, listened to and so on.(Brown & Levinson, 1987:129) Data 8: (A)Maid: ((take the bags and case)) (B)Suu: “Give it[bag] to me ((smile)) In this extract above, S seems like command H directly. But it is uttered softly, because S act her speech while smile to H. Here, S makes communication with H [maid], as usual the maid always serves the house well, H brings S’s bag, but S ignore H’s act. The ignorance states in positive way, then for intended action S asks H as in Give it[bag] to me. This sentence represents S want that she gives gifts to H, the gift may not a good but something like sympathy or understanding that H has been done a lot of things well, so that S does not want to burden H more. d.Avoid disagreement, In order to satisfy h’s positive face, S should avoid disagreement with H. One strategy to achieve such circumtance is by pretending that S agrees with H’s statement. It called ‘token agreement’. For example Data 11: (A)Guest: “Madam, it’s urgent, we believe that you are the best figure to bring this country in democracy” (B)Suu: “Beside my less experience, I had leaved this place for long time, so I think, I need you to…” In the case of (data 11), S disagree with H wants. It shows by using “Beside my less experience, I had leaved this place for long time” Before this statement appears, H wants S to lead and join against military government, but S disagree. S feels do not confidence with those agreement. As consequence S intends her utterance by saying “so I think, I need you to…. S avoids H’s agreement, but at the end S seems like agree, however in condition where H has to do something for S. it is like accepting through ignorance words, or in other words “yes, but…”. e. Offer promise, Stressing that whatever H wants and will help to obtain. S may state offers and promise to create such condition with a purpose of showing S’s good intentions in redressing H’s positive face wants even if they are false. Data 27: (A)Suu: ((Walk to the gate)) (B)Soldier: “hei, no you can’t, stop! (A’)Suu: “What? I just want to talk with them, never try to bother me, I will talk with them” ((meet her supporter outside the gate)) “offer promise” can be applied as in data 27. S says “I will talk with them” this utterance seems like intimidates H. S creates condition with a purpose to against H. S stresses it utterance with give exact meaning of “I will talk with them and everything will be alright, you save and I save, so please don’t stop me”, S may want H fulfill her wants by showing positive sentence to H even if they are false. f. Give reason, Giving reason is a way of implying’ I can help you’ or ‘you can help me, and assuming cooperation, a way of showing what help is needed. This fact directs to pressure to go off record to investigate and see H whether or not he is cooperative. Data 20: (A)General Nyunt: “you are a good wife also a good girl, after your mother passed away, surely you want to go home soon to meet your kids and husband right (B)Suu: “I think you haven’t to do it [drive away] General Nyunt. Now, my big mission in Burma is joining in the national election. As soon we held the election, as possible I will beside them [family]. You may suggest Ne-Win in hurry.” This strategy implies that if S has good reasons why H couldn’t cooperate. This strategy can also be used to criticize H’s past action why he did or didn’t something without any good reason. In the other words S tries to criticize why H do not held election soon. H should do it if they want S leave soon. Here, S wants to give indirect suggest to H through positive and cooperative way. g. Use in-group identity maker, This strategy suggests that claiming implicity the common ground with H, S can use in-group membership identity maker. The address form includes generic names and terms like mac, mate, buddy, pal, honey, dear, cutie and guys. S claims common ground with H by showing that both of them in the same group of level and sharing particular desiring such as values and goals. This strategy shows as in extracts below. Data 23: (A)Suu: “My darling, I hear violence that conducted by Ne-Win military soldier happen every day. They want to found the authority with that way. So you can’t back here in this time, so darling please, do your best, and don’t worry about me.” (B)Husband: ((seeing Suu, silence but thoughtful)) This strategy uses not only to make solidarity, but also emphasize make the communication flow in informal style since it is minimize status differences. h.Assert/presuppose S’s knowledge of concern for H’s wants, This strategy is declaring or employing knowledge of H’s wants and willingness. In the data 24, utterance “there are many soldiers around our house” shows presuppose S’s knowledge about the situation they faced. Then, S asserts of concern for H’s wants is associated in maybe there’s nothing happen. However, if I’m caught, I had arranged plan to send you back to Oxford. S puts a pressure on H to cooperate with her. Cooperate here meant if something happen because of S’s presupposition, S wants H do something that had been arranged by H. All of utterances stated by S are significant to H’s wants, the want of to be safe. Data 24: (A)Suu: “Good morning, get up boys, how was your sleep? Listen, today, this morning, there are many soldiers around our house. I don’t want you be afraid, maybe there’s nothing happen. However, if I’m caught, I had arranged plan to send you back to Oxford. I want you to know, everything will happen, we still love you. Ok?” (B)Children: “Yes mom” i. Seek agreement, This strategy can be achieved by S in raising safe topics. By doing ‘safe topic’ S is allowed to stress his agreement with H and satisfy H’s want to be right or to be corroborated in his opinion. Small talk about weather, sickness, politic, and current local issues. seek agreement are some example of ‘safe topic’. Data 29: (A)Suu: “Is it may a new face? ((talk to a soldier)), what’s your name? ((pause)) do you speak English? So what’s your name?” (B)Soldier: ((Smile)) To make good impression S uses small talk as initial of the conversation. This strategy also has big role of successful S’s purpose and avoid the ignorance. j. Exaggerate, This strategy quite similar to the attend to H’s interest, wants, needs, goods strategy however, S’s attention or sympathy to H is indicated by exaggerating intonation, stress, and other aspect prosodic such as marvelous, the best, how beautiful etc. Data 32 (A)Suu:”You might be the best husband ever after.((hug Mikey)) (B)Husband: I will ((smile)) S’s strategy also indicates a hope, S has big hope to H to do something. S wants H to be the best husband ever after for S. Its desire is spoken by giving H interest or attention in form of exaggerates. 2. The Types of Request and Command Used by Aung Saan Suu Kyi 2.1 Request, It is concern in the types of request utterances built by speaker in her utterances which may belong to positive or negative politeness. a. (-) Query preparatory, That is request utterances which contain reference to preparatory conditions such as ability and willingness, as conventionalized in any specific language. As in data 1 below, S requests for telling story. Data 1: (A)Suu: “Dad, tell me a story please” (B)Suu’s Father: “I will tell you about Burma” The sequence of the sentence contains of address term “Dad” and query preparatory “tell me a story please”. Here, S places the word “please” in the end of the request, means that she wants to ask H in polite way, however she begins her request by first form of verb “tell”, S forms her request by showing her willingness that H can fulfill her request. (+) Query preparatory there was distinguish feature of utterances belong to the positive tend to spoken by participant who want to get closer relationship, and both speakers want the same thing. This condition also place indicate that the utterances is speaker and hearer oriented. b. (-) Strong hints, This category forms request utterances which contain partial reference to object or element needed for the implementation of the act. References used significant to hints the requests because S do not want to impose H’s face S wants H learn the reference by themselves to know what S wants then understanding it to take extended acts to fulfill S’s requests. However, actually the extended acts are not important, the important one is the function of the reference itself. S also uses will and conditional if associate to the hint request which is imply to the negative politeness. c. (-) Obligation statements, That is request utterances which the obligation of the hearer to carry out the act stated explicitly. It is proven by using of first form of verb like “be” and “help” S really wants H to do her request, this characteristic belongs to negative politeness strategy because of the using of positive statement which means S obligate H to do something in the way of giving good impression to H. d. (-) Mild hints, That is request utterances which does not contain reference to the request form properly, but it is interpreted as request by context. The request formed immediately go on head act, there is neither supportive move as reference nor address term. The request provided on interrogative form e.g:“What are you doing?” which it does not mean to be answered. That is a request S formed to H in order to follow S’s want. At glance, there is not like a proper request, but based on the language function, it is structurally incorrect then, functionally proper. e. (-) Suggestory formulae, That is request utterances which refer to suggestion to the hearer to do act. As provided in data 34A, S tries to give suggestion to H. In the fact, that suggestion is a request form. The request made seems like contains a worry. S gives suggestion whether she’s coming is needed by H. her worry appears because she cannot insure her request will be fulfilled or not by H. So that, in the name of does not want to impinge H, S make her request in the suggestion form. This suggestion belongs to the characteristic of negative politeness strategy, the evidence is the using of modality “should” it associates to the utterances which suggest or need an agreement from H to fulfill the request. (+) Suggestory formulae in positive was strategy formed by using future desire of “will”. Besides that, the role of “we” as in “let we take her to the bed, then we will see what’s going on and in the ““We can start it?” As sign that between S and H include in the same activity strengthen its position belongs to positive politeness strategy. This request S’s characteristics is giving suggestion to H to do the thing together. f. (-) Hedge performative, That is request utterances in which the illocutionary force is named and accompanied by hedging expressions. There are address term such as “Buddhist, Burmese”. Then, followed by supportive move that spoken in long sentence as references of S to ensure H, it was an effort to make sure that implicit requests which spoken successfully listened. (+) Hedge performative, Elements by means of which the speaker avoids specification in making a commitment to the illocutionary point of the utterance, in naming the required action, in describing the manner in which it is to be performed, or in referring to any other contextual aspect involved in its performance. This request category has characteristic which S tries to give “softening” effect to her request. 2.2 Command, Command in language use, is used to ask something with obligate answer. S has strong desire which has to do by H either negative or positive politeness has command utterances. a. (-) Most direct, That is explicit level, realized by command syntactically marked as such, such as imperatives, or by other verbal means that name the act as command initial first form of verb. the command utterances form by S is obeyed by H, because H treats in duty. (+) Most direct This level of command used in positive by S with provides some additional sign which indicate to the positive. It may same as negative that contains first form of verb like in the “Give it[bag] to me” S commands H to do something that it decrease H’s duty or as simple words, S want to help H under the term of command. b. (-) Conventional Indirect This command’s level procedures that realize the act by reference to contextual preconditions necessary for its performance, as conventionalized in a given language (these strategies are commonly referred to in speech act literature. This command utterances is not as strong as most direct one, because speaker formed her command with negation and modality S wants to show power through command, but she does not want to impinge the hearer. That’s why this command belongs to negative politeness strategy. (+) Conventional indirect, command that contain invitation by calling H with first name (FN), it also can contain good impression to get H closer obviously get good responds of the command formed. the impression brought H to fulfill what S wants. However, there a “must” that contain a duty, H accepts it happily because there are prize for H. c. (+) Non-conventional indirect level, i.e. the open-ended group of indirect command (hints) that realize the command by either partial reference to object or element needed for the implementation of the act. This level contained softening command or hidden command. S forms command by using “will” as characteristic of soften command. E.g: “I will campaign…” and “never try to bother me, I will talk with them” are example implicit command used by S. To show the positive strategy, S forms the command characterized as making agreement, that is cooperation among participants to fulfill the wants. 3.How does Aung San Suu Kyi influence the addressees in order to get good responses? This part analyzed findings in previous problems which influence the hearers’ responses. 3.1 Different function of “please”, In communication people used term please for a willingness statement. It is so as in Suu’s statement in the film, she used please for hoping something, and emphasizing the willingness. Please can be stated in front of statement or in the end. In this part subject produced word please differently. Based on the theory of request (Blum-Kulka:1987) “please” used to express hoping for something with full of willingness. The subject of the film used the function of please to utter strong request. In other situation please only for “sweetener”, because there was no strong willingness occurred. Suu gave new function of please in this movie. It was different from the other study conducted request as theory which it put please only as negative politeness marker without mentioned the distinctive function. This finding showed that request utterances with please indicating social relationship where speaker put herself in higher or lower position than hearer. It is supported by theory of power relation by (Fairchlough:1989) that type of this please request tend to use by younger to elder. And Suu applied it both while talking with elder and younger. In this case Suu showed that please was not stuck in the using. In this movie subject shows that type of please used in different purpose. 3.2 Universality of “thanks”, The using of thank commonly used for saying thank you for people that help or doing something for us. Involving thank words in to utterances was one of negative politeness strategy. It based on (Yule: 65), thanks could work sometimes be heard in extended talk often with hesitations. In this study, subject represented thank in apologize and gave deference. They reflected the differences of using thank or I prefer to call it universality of thank. Subject defense the theory, the possible reason was subject to show the wants differently or there were factors that force speaker (S) to use it in other sentences besides thank sentences. Universality of using thank reflected apologizing utterances also contrast to the previous study conducted by Wagner which apologizing occurred did not showing thank word. The other function of thank is used for showing deference. Deference communication appeared when S felt H need to be honor. In the case of Suu’s utterances, the honorific by using thank used was as same as Brown & Levinson theory which it had function for talking to the far relationship, and if it said to the people close relation, it was not an honor, but it would be a purposeful way. Obviously, thank is universal in its using. Thank not only used for saying thank you, but also, subject in this film shows us that thank can be used to show apologize and showing deference. 3.3 Different function of inclusive “we”, Based on Brown & Levinson (1987) theory we used in positive refer to main purposes of making solidarity, need to be accepted, even liked by others and to be treated as member of same group. It is same with purpose in data of inclusive we uttered by Suu. Positive-we which “we” tends to put speaker (S) and hearer (H) include in same activity. Positive-we used to built solidarity in communication. Both S and H are involved in the same topic spoken. Positive-we ask H to join in the speaker’s wants or S joins to the H’s wants. Here, “we” used as signal of good cooperation among of participants. In this case, positive-we have same purpose like the previous study conducted by Ayuningtyas which concern to the associate responses of children. However the hearer was different, but both this study and that previous research had same purpose. That way appropriate used to show togetherness among speaker and hearer. Otherwise, we used in negative reflected differently. They are refer to the negative politeness which have main purposes oriented to show deference, need to be independent to have freedom of action, showing respect to others, or sometime negative utterances more formal than positive one. It is proven through S uses negative-we in her political campaign where it is a formal situation. Actually, the negative-we used by S is represent if “I”. Speaker wants to avoid personalize term of “I”, so that she uses negative-we, because, when S uses “I” in formal situation. it Negative -we also shows that S cares about H’s wants without impinge on H’s negative face. The discussion shows us that inclusive “we” can be used both in positive or negative, which positive-we has function of making good cooperative communication or solidarity in same group, while, negative-we has function of represent “I” to avoid personalize, and also to show using polite pronoun in formal activity. 3.4 Different function of query preparatory (QP), suggestory formulae (SF), and hedge performative (HP) in (-) & (+) Difference of QP in negative, or it called as “–QP”, it is request category which has characteristic of preparatory conditions. The request sequences are only oriented to S (speaker) wants. These are different from QP in positive, or it called as +QP. The difference of SF in negative it called as –SF. Request category which contains suggestion. Characteristic formation used by S is using suggestion through word “should” used by subject is modality form, modality sometimes shows respect, because it is more polite than “shall or will”. So that she makes it as –SF to avoid impinge H. It is different from SF in positive that it called +SF. Request sequence formed with using “will”. The request type used by S included both S and H in the same activity to gain same wants. It was S (speaker) and H (hearer) oriented. Then, difference in request is HP, this category appears either in negative that it called as –HP or in positive that it called as +HP. The differences of –HP and +HP state in the request function based on condition. S made implicit request in order to reach successfully listened, S used the function of upgrader. The upgrader means S and H had separation, where S here in the “up” or high position that has possibility (power). Upgrader function suggests S to persuade H fulfilled what her wants. These are different from the using of request in +HP. This request category has characteristic which S tries to give “softening” effect to her request. +HP also has function of downgrader. This condition is opposite to the –HP that has upgrader function. Downgrader places herself in lower position and down tone utterances than H. It’s happen because of S wants to make “softening” request. That “softening” formed through +HP and it significant to help request become downgrader. The three request categories showed that same category can be stated in positive or negative, as the subject in this movie shown. However they are same in the terms or names, but they have their own differences when they used in positive and negative politeness. 3.5 The formulation command utterances in most direct(MD), conventional indirect(CI), and non-conventional Indirect(NCI). a. First level is most direct or easier to call it MD. It is direct command or I prefer call it “strong command”, because this command directly point the purpose out. Speaker (S) directly mentions what thing becoming point of command. Usually MD level using imperative to state command utterances. That was the using of first form of verb put in the beginning of the sentences. That’s why it assumed that MD level contains command formulation: Verb 1 as starting words of command, as example: Data 8: (A)Maid: ((take the bags and case)) (B)Suu: “Give it [bag] to me ((smile)) b. Second level of command was conventional indirect, or it called as CI. It is the middle of direct command which means CI is not too direct and also not too indirect. This means S formed command with some purposes, for example S wants to get closer with H or doesn’t want to impinge H. The other purposes may S want to showing appreciate to H. Usually these command level has additional information / supportive sentence which following command in order to make commands did not sound too strong. They can be stated before or after command uttered. Supportive sentence / additional information can be contained of; modality, address or first name (FN), and making good impression. CI examples below have command formulation: supportive sentence + command statement. Data 6: (A)Activist: ((bring a blooded girl leave her bed)) (B)Suu: “She can’t leave this place, [supportive sentence] + you should stay here”, [command] c. The last command level was non-conventional indirect or NCI. This level was similar with hints/hidden command. The formation of the utterances may not command form, but the element inside the sentences has implementation of command. Here, S want to command H implicitly, and the implicit feature forms through future desire “I will…”. It was not only to hide the command, but also to shows S’s plans, which those plans have same function as command because they bring H involve to the utterances. In the other words, S uses “I will…” to show H what her plan is, while at the same time, S also commands H to do “something”. Subject in this study used NCI level with command formulation: hints command by using “I will…”. The obvious features of how did language operate in social interaction were influential and instrumental relationship with power. Influential power found in the research closely related to the dominance words that subject used, this domination mostly appears in command utterances. The position as political leader has big potential to influence the responds of the hearer whom talks with. The ability of influencing people in communication cannot be separated from successful sequences both in request and command used which well formed. The strategies used associated to the instrumental. They were like the useful tools to dress utterances being interesting, or interested in hearer. The subject capability of matching many instruments as instrumental power to gain the goal influenced to the hearer was a kind of creating power language process, so that subject had powerful language in achieving successful responses. CONCLUSION AND SUGGESTION Conclusion This study can be concluded that, first politeness strategies used by subject Aung San Suu Kyi in the film “The Lady” are both positive politeness and negative politeness. Subject implements their sub-types, but not for all types. From fifteen sub-types of positive provided, subject used ten sub-types, and from ten sub-types of negative provided, subject used seven sub-types. Second, the characteristics of the subject that have been measured by request and command, politeness characteristics resulted are; in request, there are query preparatory, strong hints, mild hints, obligation statements, hedge performative and suggestory formulae. In command, there are most direct, conventional indirect, and non-conventional indirect. Third, the influences of subject’s utterances are defined from the responses given to subject, and how far subject’s strategies influence others are taken from analyzing them through content, subject, and relation. Suggestion It was suggested that the later research can conduct the same research in other aspect of discussion, for example by conducting the research with real situation as the object. It was hoped the next study would observe some politeness strategies with different backgrounds in order to know the characteristics of politeness strategies in different ways. REFERENCES Ayuningtyas, D. 2006. Politeness Strategy in Request in Film Harry Potter, and The Related The Associated Response in Children Character. English Department, State University of Surabaya. Blum-Kulka, S., and Olshtain, E. 1987. Requests and Apologies: A Cross-Cultural Study of Speech Act Realization Patterns (CCSARP)1. Hebrew University, Jerusalem Tel Aviv University. pdf. file, Journal of Applied Linguistics, Vol. 5, No. 3 (pp:196-212) Brown, P., and Levinson, S. 1987. Politeness Some Universals in Language Usage. Cambridge: Cambridge University Press Codreanu, A., and Debu, A. 2011. Politeness in requests: Some Research Findings Relevant for Intercultural Encounters. pdf. file, Journal of Defense Resources Management no.2 (2)/2012 Fairclough, Norman. 1989. Language and power. Edinburg: Longman Fairclough, Norman. 2012. Critical Discourse Analysis. International Advances in Engineering and Technology (IAET) ISSN: 2305-8285 Vol.7 July 2012 International Scientific Researchers (ISR) Holmes, Janet. 2001. An Introduction of Sociolinguistics. Edinburgh: Longman Leech, Geoffrey. 1983. The Principles of Pragmatics. New York: Longman Litosseliti, Lia. 2010. Research Method in Linguistics. London: Continuum International Publishing Group Magnis-Suseno, Franz. 2009. Etika Jawa: Sebuah Analisa Filsafat Tentang Kebijakan Hidup Jawa. Jakarta: Gramedia McGinty, Sarah Myers, Ph.D. 2001. POWER TALK Using Language to Build Authority and Influence.New York: Warner Books Pranowo. 2009. Berbahasa Secara Santun. Yogyakarta: Pustaka Belajar Robinson, W.P. 1972. Language and Social Behavior. Middlesex England: Penguin Book Ltd. Van Djik, T. 1995. Aims of Critical Discourse Analysis. Journal of JD Japanese Discourse vol:1 (pp;17-27) Watts, Richard J. 2003. Key Topics in Sociolinguistics: Politeness. Edinburg: Cambridge University Press Wagner, Lisa C. The Journal of Politeness, University of Lousville. Positive- And Negative Politeness Strategies: Apologizing In The Speech Community Of Cuernacava Mexico. pdf. file posted 02/18/2013 Werda, Sukardi. Politik Dan Rekayasa Bahasa (Journal of politic and language). Posted on 2nd November 2012 Wodak, R., and Meyer, M. 2008. Critical Discourse Analysis: History, Agenda, Theory, and Methodology. pdf. file Wodak-3795-Ch-01:Wodak-3795-Ch-01.QXP 9/29/2008 4:29 PM Page 1-33 Yule, George. 1997. Pragmatics. Oxford: Oxford University Press